KAJIAN ADOPSI PENERAPAN TEKNOLOGI PUPUK ORGANIK KASCING DI DAERAH SENTRA PRODUKSI SAYURAN KABUPATEN TABANAN - ., Suharyanto; Kariada, I Ketut (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2011)
Adoption Analysis on The Application of Organic Casting Fertilizer at Area of Vegetables Production Centre in Tabanan District. Adoption of organic casting fertilizer technology applied at upland vegetables centre in Baturiti District of Tabanan Bali has been evaluated. The aim was to reduce the intensive use of chemical fertilizers where research on integration of crops and livestock farming systems was implemented since 2002 until 2005. Data was collected by survey in March to June 2004 whereas 35 farmer cooperators were involved. Types of data collected were characteristics of farmers, farmers intends to adoption, technology application, and crops production. This research was purposed to gain information on the adoption of organic casting technology and the impact of research activities on vegetables production.The data was analyzed using descriptive analysis in the form of quatitative and qualitative data by scoring techniques. Research result showed that average knowledge of farmers on innovation of organic casting fertilizer was very high (86.64%), and farmers attitude to technology innovation was classified agree with percentage score of 82.44%. Productivity of vegetables increases compared to manure application. For the sustainability adoption of organic casting fertilizer, therefore required: (1) increasing the ownership of cattle, (2) continued guidance by extension workers since preparation, harvest until products marketing, (3) existing guaranty, stable and good price due to organic products, (4) the existing of awareness and participation of farmers or farmers group, and (5) supporting from local Government.Kajian adopsi penerapan teknologi pupuk organik kascing di daerah sentra produksi sayuran ini merupakan evaluasi dari kegiatan pengkajian sistem usahatani integrasi ternak sapi potong pada usahatani sayuran di lahan kering dataran tinggi beriklim basah Kabupaten Tabanan tahun 2001-2003.Pengumpulan data dilakukan dengan metode survei pada bulan Maret-Juni 2004 terhadap 35 petani responden. Data yang dikumpulkan meliputi karakteristik petani, perilaku petani terhadap adopsi, penerapan teknologi, serta produktivitas tanaman. Kajian ini bertujuan untuk memperoleh informasi: tingkat adopsi teknologi pupuk organik kascing dan dampak kegiatan pengkajian integrasi ternak sapi potong pada usahatani sayuran terhadap produktivitas sayuran. Data dianalisis secara deskriptif baik kualitatif maupun kuantitatif dengan teknik skoring. Hasil kajian menunjukan bahwa rata-rata tingkat pengetahuan petani tentang inovasi pupuk organik kascing termasuk dalam kategori sangat tinggi 86,64%, sedangkan sikap petani terhadap inovasi teknologi pupuk organik kascing termasuk dalam kategori setuju, dengan persentase pencapaian skor 82,44%. Produktivitas beberapa komoditas sayuran juga meningkat dibandingkan dengan pupuk kandang biasa. Agar adopsi teknologi pupuk organik kascing dapat berlanjut, maka diperlukan : (1) meningkatkan jumlah kepemilikan ternak sapi, (2) bimbingan oleh petugas terus-menerus, sejak persiapan, panen hingga pemasaran hasil, (3) adanya jaminan harga yang layak dan stabil mengingat produk yang dihasilkan petani dilokasi pengkajian sudah mengarah pada produk pertanian organik, (4) kesadaran dan partisipasi petani sendiri, serta (5) dukungan pemerintah daerah.